The roles of glutaredoxin GRXS17 in improving chilling tolerance in tomato and drought tolerance in rice via different mechanisms - Hu, Ying (Kansas State University, 2015)
Abiotic stresses, including chilling and drought stresses, are considered to be major limiting factors for growth and yield of agricultural and horticultural crops. One of the inevitable consequences of abiotic stresses is the accumulation of reactive oxygen species (ROS) in plants. ROS can either act as an alarm signal to induce the defense pathway when kept at a low level or cause oxidative damage to various cellular components when increased to a phytotoxic level. Glutaredoxins (GRXs) are members of ROS scavenging system that can maintain the cell redox homeostasis by using the reducing power of glutathione. In this research, we characterized the roles of GRXs in protecting tomato (Solanum lycopersicum) from chilling stresses and rice (Oryza sativa L.) from drought stresses. Our results indicated that ectopic expression of an Arabidopsis gene AtGRXS17 in tomato could enhance the chilling tolerance by increasing antioxidant enzyme activities and reducing H₂O₂ accumulation to ameliorate oxidative damage to cell membranes and photosystems. Furthermore, AtGRXS17-expressing tomato plants had increased accumulation of soluble sugars to protect plant cells from dehydration stress. In rice, silenced expression of a rice glutaredoxin gene OsGRXS17 was used as a reverse-genetic approach to elucidate the roles of OsGRXS17 in drought stress tolerance. Our results showed that silenced expression of OsGRXS17 conferred improved tolerance to drought stress in rice. ABA-mediated stomatal closure is an important protection mechanism that plants adapt to a drought stress conditions, and H2O2 acts as secondary messenger in ABA signaling to induce the stomatal closure. Silenced expression of OsGRXS17 gave rise to H₂O₂ accumulation in the guard cells and promoted ABA-mediated stomatal closure, resulting in reduced water loss, higher relative water content, and consequently enhanced drought tolerance in rice. This research provides a new perspective on the functions of GRXs in chilling and drought stress tolerance of tomato and rice, and an important genetic engineering approach to improve chilling and drought stress tolerance for other crop species.
Keywords: Glutaredoxin; Chilling; Drought; Reactive oxygen speices; Abscisic acid; Agriculture, General (0473); Biology, Plant Physiology (0817); Molecular Biology (0307)